Interpretasi Qiwamah dalam Tafsir Klasik dan Kontemporer: Analisis Keadilan Gender Berbasis Maqashid Al-Syari‘ah - Zakiyah Laili Maghfiroh; Kharis Nugroho (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to analyze the concept of gender justice in Islamic family law through the perspective of maqashid al-syari’ah, with a particular focus on the concept of qiwamah. The main issue addressed in this research is the tendency to interpret religious texts literally, which often leads to unequal relations between husbands and wives in family life. This research employs a qualitative method with a normative approach based on library research, by examining classical exegetical works such as those of At-Ṭhabari, Ar-Razi, and Wahbah Az-Zuḥaili, and relating them to contemporary social realities. The findings indicate that the concept of qiwamah in classical interpretations is not understood as an absolute form of male superiority, but rather as a functional responsibility related to social and economic aspects. The maqashid al-syari’ah approach provides a more contextual analytical framework by emphasizing public welfare (maṣlaḥah) as the primary objective of Islamic law. In this perspective, the relationship between husband and wife is viewed as a partnership based on justice, cooperation, and mutual consultation. Therefore, gender justice in Islamic family law is not defined as absolute equality of roles, but as a fair, proportional, and contextual distribution of rights and obligations, enabling Islamic law to remain relevant and responsive to social dynamics.